Enterprise Resource Planning (ERP) Evaluation and Implementation: A Case Study - Yosevine, Prisca; Oetama, Raymond Sunardi; Setiawan, Johan; Princes, Elfindah (APPS Publications, 2021)
Objective – To understand the success rate of ERP in the company by using the Ifinedo method and provide proposals that can improve ERP implementation in the company based on the unfulfilled Ifinedo method. Methodology – This research uses Quantitative method research distributed to 50 end users at Indoporcelain using surveys and interviews. Findings – The research found one point that is less valued in the company, namely vision and mission factors in organizational variables compared to other factors. Therefore, proposals in this sector are indispensable in order to increase the success of ERP implementation in the company. Furthermore, lack of IT support due to the management’s ignorance has made the ERP implementation did not reach the optimum performance expected. Novelty – By measuring the success rate of ERP in the company, the company can know how the success rate of ERP implementation in its company. The company can make corrections and quality improvements to existing ERP systems based on proposals with unmet Ifinedo method.